Determinant of Foreign Direct Investment G-20 Countries - Ashari, Nesha Rizky; Qodhari, Dafelia; W, Irwan; Fahira, Khadhiya; Wau, Taosige (Jurnal Ekonomi Pembangunan, 2025)
Foreign Direct Investment (FDI) has long been identified in the empirical literature as a potential contributor to economic growth and is considered an important source of capital in both developing and developed countries. This study aims to identify and analyze the determinants of FDI in G-20 countries, taking into account variables in economic, socio-political, and institutional contexts. This research offers a more comprehensive approach by integrating economic, socio-political, and institutional dimensions into a single panel analysis model. This research contributes to the literature through a more holistic understanding of the factors influencing FDI flows in G-20 countries. Based on the analysis of the data regression panel, results were found that any increase in the labor force and political stability of G-20 member countries will encourage an increase in the value of FDI in those countries. Meanwhile, interest rates, economic scale, and financial development do not show a significant influence on FDI in G-20 countries. The findings of this study provide important insights for policymakers in G-20 countries in developing strategies to increase FDI attractiveness by taking into account the key factors that have been identified. These results can also assist international investors in making more informed decisions related to the location of their investments, taking into account the dominant economic aspects in attracting FDI